SMART TECHNOLOGIES AS A TOOL FOR FORMING THE COMPETENCES OF UNIVERSITY STUDENTS - Allaberganova Muyassar Rimberganovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article reveals the concept of “smart education” and its definitions given by scientists, its place in the educational process and the essence of this educational system, as well as general information about its basic principles. Opinions are described on the creation of educational resources using smart technologies in higher educational institutions and the formation on this basis of students' knowledge, abilities, skills and competencies.